Topical Delivery of 5-Fluorouracil from Pheroid™ Formulations and the In Vitro Efficacy Against Human Melanoma - Chinembiri, Tawona N. (AAPS PharmSciTech, 2015)
Drug delivery vehicles can influence the topical delivery and the efficacy of an active pharmaceutical ingredient (API). In this study, the influence of Pheroid™ technology, which is a unique colloidal drug delivery system, on the skin permeation and antimelanoma efficacy of 5-fluorouracil were investigated. Lotions containing Pheroid™ with different concentrations of 5-fluorouracil were formulated then used in Franz cell skin diffusion studies and tape stripping. The in vitro efficacy of 5-fluorouracil against human melanoma cells (A375) was investigated using a flow cytometric apoptosis assay. Statistically significant concentrations of 5-fluorouracil diffused into and through the skin with Pheroid™ formulations resulting in an enhanced in vitro skin permeation from the 4.0% 5-fluorouracil lotion (p < 0.05). The stratum corneum-epidermis and epidermis-dermis retained 5-fluorouracil concentrations of 2.31 and 6.69 μg/ml, respectively, after a diffusion study with the 4.0% Pheroid™ lotion. Subsequent to the apoptosis assay, significant differences were observed between the effect of 13.33 μg/ml 5-fluorouracil in Pheroid™ lotion and the effects of the controls. The results obtained suggest that the Pheroid™ drug delivery system possibly enhances the flux and delivery of 5-fluorouracil into the skin. Therefore, using Pheroid™ could possibly be advantageous with respect to topical delivery of 5-fluorouracil.